Acceptability of a Proposed Marine Protected Area: A Precondition for Marine Biodiversity Conservation Efforts in Ozamiz City, Philippines - Galindo, Russel P. (Future Science / FSH-PH Publications, 2024)
A clearer understanding of human or social aspects of environmental issues will enhance conservation. While social acceptance is critical in determining MPA success, it continues to be an inadequately explored area of research. This study examined the acceptability of the proposed Marine Protected Area in Ozamiz City, Philippines. Stressing the significance of social acceptability to an MPA's successful implementation, this investigated the influence of the fishing households' knowledge of the marine environment and coastal resource management and the perceived condition of the coastal environment on the social acceptability of a proposed MPA implementation. The study used a mixed-method, particularly concurrent triangulation design, utilizing a sample of 270 fishing households in the 15 coastal barangays of Ozamiz City. The data were gathered through a survey supplemented with key informant interviews (KII). The study revealed that the knowledge of the marine environment and coastal resource management had shown a highly significant relationship and emerged as a predictor of the social acceptability of the proposed MPA. Therefore, greater knowledge of the marine environment and coastal resource management among the fisher folks and stakeholders, in general, may result in a higher level of acceptability of the proposed MPA, thus resulting in a successful implementation. Strategies must be implemented to enhance and enrich the fisher folks' knowledge of the marine ecosystem and coastal resource management. Information on the features, characteristics, and importance of the corals and coral reefs to the marine ecosystem should be emphasized.